Crosslinked Nanofiber‐Reinforced Solid‐State Electrolytes with Polysulfide Fixation Effect Towards High Safety Flexible Lithium–Sulfur Batteries. (3rd August 2022) - Sheng, Jinzhi; Zhang, Qi; Sun, Chongbo; Wang, Junxiong; Zhong, Xiongwei; Chen, Biao; Li, Chuang; Gao, Runhua; Han, Zhiyuan; Zhou, Guangmin
Abstract: Solid‐state lithium–sulfur (Li–S) batteries using gel polymer electrolytes have attracted much attention owing to their higher safety compared to liquid electrolytes and lower interfacial resistance compared to ceramic electrolytes. However, except for their unsatisfactory lithium‐ion conductivity, relatively low mechanical strength, the unavoidable polysulfide shuttling in gel polymer electrolytes still limits their development. This work designed a poly(ethylene oxide)‐polyacrylonitrile (PEO‐PAN) copolymer membrane electrolyte, in which PAN fibers act as both a filler and crosslinker. This structure not only provides improved ionic conductivity, high mechanical strength, and lithium dendrite blocking ability, it also inhibits polysulfide shuttling as a result of strong polysulfide adsorption by the CNO functional groups formed during the PEO and PAN crosslinking process, which improves the safety, cycling stability and rate capability when used in Li–S batteries. A more than 96% capacity retention after 1000 bend cycles of the flexible battery is also achieved because of the high flexibility and high bonding strength of this electrolyte. Abstract : The poly(ethylene oxide)‐polyacrylonitrile‐based gel electrolyte with a crosslinked structure has a high ionic conductivity and high lithium salt dissociation ability. The newly formed nitrogen‐containing groups after crosslinking provide stronger polysulfide adsorption, which inhibits polysulfide shuttling. The high bonding strength of this electrolyte yields a stable electrochemical performance of flexible lithium–sulfur batteries in the bent state.